You’ll never walk alone: designing a location-based soundtrack - Hazzard, Adrian; Benford, Steve; Burnett, Gary (2014)
Musical soundtracks have great potential to enhance mobile walking experiences such as tours and guides, much as they already do for films and games. They also raise new challenges for composers as the music must fit a given landscape and respond to walkers’ trajectories. We present a design for an interactive mobile soundtrack to accompany a visit to a sculpture park. We describe the motivating factors used to structure soundtrack and drive the compositional process.